The roles of artificial intelligence and knowledge management in emergency telecommunications - Ei, Sun Oh; Chai, Madeline; Ei, Fun Oh (2004)
Over the past decade, the international community has recognized the substantive role modern telecommunications can play in disaster relief operations and humanitarian actions.The Tampere Convention on “Emergency Telecommunications” was an initiative to facilitate these activities, endorsed by various international conferences.The role of artificial intelligence and knowledge management in emergency telecommunications could be tremendous, with applications potentially ranging from network and workflow management to training and decision support.In the future, a greater convergence among different technologies, artificial intelligence and knowledge management included, in the service of emergency telecommunications could be foreseen, thus achieving the noble goal of utilizing modern information and communications technologies for disaster mitigation.